A Study of Systemic Variation and Frequency of Modified Idioms In Forbes Asia and The Economist (International Journal of Language, Literacy and Translation, 2025)
Modified idioms or idioms with variation are figurative language that pose many semantic problems especially to non-native speakers of English. Apparently, a change in idiom form causes the message to be misunderstood by the non-native speakers as they lack familiarity of the modified idioms. Therefore, this case study aims to investigate the type and frequency of systemic variation of modified idioms found in Forbes Asia and The Economist. Glucksberg’s (2001) textual analysis framework on modified idioms is applied as part of the qualitative analysis. The results of the study indicate that omitted, modified idioms with noun variation, and modified idioms with verb variation are types of systemic variation of modified idioms that are familiar to users. The findings of this study contributes toward identifying the type and frequency of modified idioms which affect familiarity and comprehension among readers of Forbes Asia and The Economist. Thus, the promotion of variation of modified idioms should focus more on types of variations with none or limited emergence of familiarity.